1982
DOI: 10.1103/physrevb.25.6595
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer study of magnetic properties in low-stage FeCl3intercalated graphite

Abstract: Using relaxation theory, we have completed the first fits to the broadened Mossbauer spectra observed about the magnetic transition temperature in stage-1 and -2 ferric chloride intercalated graphite compounds. We conclude that the major Fe3+ site undergoes a magnetic phase transition at 4.2 %0.5 K for the stage-1 compound and 2.0 21.5 K for the stage-2 compound. These results are significant in showing that the magnetic phase transition, at least in the stage-1 compound, is strongly influenced by three-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…2,4,[12][13][14][15][16] Millman and Kirczenow 16 have shown that there are three kinds of Fe site in the FeCl 3 intercalate layers of stage-1 and stage-2 FeCl 3 GIC's. Their results for stage-2 FeCl 3 GIC are as follows.…”
Section: A Mössbauer Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,[12][13][14][15][16] Millman and Kirczenow 16 have shown that there are three kinds of Fe site in the FeCl 3 intercalate layers of stage-1 and stage-2 FeCl 3 GIC's. Their results for stage-2 FeCl 3 GIC are as follows.…”
Section: A Mössbauer Effectmentioning
confidence: 99%
“…The magnetic properties of FeCl 3 GIC's have been studied by many researchers for almost three decades. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The pioneering work of the magnetic study on FeCl 3 GIC's was made by Karimov and co-workers. 1 They showed that the magnetic susceptibility of polycrystalline samples has a peak at 3.6 K for stage-1 GIC and at 7 K for stage-2 GIC, which is identified as the onset of antiferromagnetic and ferromagnetic phase transitions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] As an anode for the Li-ion batteries, the stage 1 and stage 2 FeCl 3 -GICs deliver reversible capacities of 813 and 525 mA h g À1 , respectively, after 100 charge/discharge cycles. FeCl 3 -GICs were used in rechargeable Li-ion batteries, which exhibited high capacities and long-term cycling stability.…”
mentioning
confidence: 99%
“…FeCl 3 -GICs with stage 1 and stage 2 structures were synthesized by reacting FeCl 3 and expanded graphite (EG) in a stainless-steel autoclave in air, which was different from previously reported methods. [16][17][18][19][20] As an anode for the Li-ion batteries, the stage 1 and stage 2 FeCl 3 -GICs deliver reversible capacities of 813 and 525 mA h g À1 , respectively, after 100 charge/discharge cycles. These properties are comparatively higher than the capacity for EG, which was 113 mA h g À1 .…”
mentioning
confidence: 99%
“…However, Mössbauer spectroscopy reveals a more complex situation. Three distinct Fe sites (A, B, and C) are found in temperature-dependent Mössbauer measurements [16,17]. The majority component originates from site A and is attributed to Fe 3+ ions [16], the magnetic moments of which lie in the basal plane [16,17].…”
Section: Introductionmentioning
confidence: 99%